Self-sufficiency in vegetables - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
With food imports costing ACP Caribbean countries twice what they receive from food exports, there is obvious opportunity for expanding production of food crops for local consumption by residents and by the growing number of tourists. In the Leeward...